2002
DOI: 10.1111/j.1741-3737.2002.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to Caregiving, Gender, and Psychological Well‐Being: A Prospective U.S. National Study

Abstract: ࡗ Transitions to Caregiving, Gender, and Psychological Well-Being: A Prospective U.S. National Study Guided by a life course perspective, this study examined the effects of transitioning into caregiving activity for a child, spouse, parent, other relative, or nonkin associate on nine dimensions of psychological well-being. Data came from adults ages 19-95, who were noncaregiver primary respondents in the National Survey of Families and Households in 1987-88 and who were followed up longitudinally in 1992-93 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
180
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(211 citation statements)
references
References 38 publications
15
180
2
4
Order By: Relevance
“…Several authors have also appealed to the possibility of the existence of positive repercussions of care (Marks et al, 2002;Ló pez et al, 2005), where several investigations have indicated an increase of expertise and the feelings of satisfaction derived from caring for a dependent person as the two most relevant positive consequences.…”
Section: Empirical Results About Caregiver Stressmentioning
confidence: 99%
“…Several authors have also appealed to the possibility of the existence of positive repercussions of care (Marks et al, 2002;Ló pez et al, 2005), where several investigations have indicated an increase of expertise and the feelings of satisfaction derived from caring for a dependent person as the two most relevant positive consequences.…”
Section: Empirical Results About Caregiver Stressmentioning
confidence: 99%
“…Whereas the current knowledge on care evaluation is mostly focused on spouses and adult children as caregivers (Kramer 1997a;Lawton et al 1991;Marks et al 2002;Pinquart and Sörensen 2011;Raschick and Ingersoll-Dayton 2004;Savundranayagam et al 2011), we added more insight into the characteristics of the group of other caregivers, a rather unexplored type of caregiver so far (cf Schulz et al 2012). In addition, the study explored the impact of many different types of correlates, which provided more insight in differential effects on burden and positive evaluation and the degree to which the caregiver stress model is applicable to both positive and negative care evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their relatively low care intensity, a lower care burden can be expected compared to spouses and adult children. Marks et al (2002) stressed that for non-kin caregivers the choice to provide care is less guided by the normative obligations that mark spousal and parent-child relationships, and is based more on consideration of perceived opportunities and costs or on a strong bond that they have developed with the care recipient. Insofar as these other caregivers may feel less obliged to provide care, their sense of burden may be lower and sense of satisfaction may be higher.…”
Section: Types Of Care Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further possibility is that sleep quality mediates the association of social relations and plasma IL-6. Our analyses tested for both moderating and mediating influences (20).…”
mentioning
confidence: 99%